PEMIKIRAN TAQIYUDDIN AN- NABHANI TENTANG PENGATURAN INTERAKSI PRIA DAN WANITA - Muhammad Kamalin (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Taqiyuddin an-Nabhani, in his work, the display settings for the social interaction of men and women. Therefore, setting the interactions of men and women with respect to employment should be examined thoroughly and deeply. An-Nabhani Taqiyuddin work is built on a number of basic views, namely: the first is changed views about men and women. Islam sees that the Almighty God created human beings, both men and women are provided with the same nature, the presence of physical needs and the same instincts, also has the potential to be equally sensible. Both are obliged to pray, fast, filial to parents, preach Islam. Both views about the legal status of male and female relationships, meetings of men and women within the framework of cooperation in the midst of life, such as in trade, education, political and ijarah. It is of necessity to realize the benefit of both of them and society in General. Therefore, the meeting and interaction should be done with the basic views and cooperation arrangements that gave birth to virtue for society and individuals, ensuring the realization of the lofty values and means God Almighty. The third position of men and women in the presence of taklif syara '. Islamic jurisprudence imposes a taklif on humans regardless of sex. The emerging issues related to the nature of kemaskulinan or kefemininan, the Sharia law in accordance with the taklif bring nature of it. For example, jurisprudence and the law about taklif bring position, fatherly roles and responsibilities only to men while the maternal position relating to only to women.